2020
DOI: 10.1523/eneuro.0268-20.2020
|View full text |Cite
|
Sign up to set email alerts
|

Behavioral Disassociation of Perceived Sweet Taste Intensity and Hedonically Positive Palatability

Abstract: The intensity of sucrose (its perceived concentration) and its palatability (positive hedonic valence associated with ingestion) are two taste attributes that increase its attractiveness and overconsumption. Although both sensory attributes covary, in that increases in sucrose concentration leads to similar increases in its palatability, this covariation does not imply that they are part of the same process or whether they represent separate processes. Both these possibilities are considered in the literature.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2
2

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 54 publications
(73 reference statements)
1
2
0
Order By: Relevance
“…As has been shown previously for rats (Grossman et al, 2008;Moran & Katz, 2014), significant learning-related changes in GC neurons recorded from control animals were largely restricted to the late epoch of the response (>750ms; Figure 4a, left). This pattern is consistent with the generally agreed-upon suggestion that CTA changes the palatability of a taste, leaving taste identity intact (Bures et al, 1998;Fonseca et al, 2020), and with the fact that it is the transition into this late state that is implicated in the driving of palatability-related behavior (Li et al, 2016;Sadacca et al, 2016;Mukherjee et al, 2019).…”
Section: The Dynamics Of Learning-related Response Plasticity Is Abnormal In the Bla-specific Stk11 Kosupporting
confidence: 88%
“…As has been shown previously for rats (Grossman et al, 2008;Moran & Katz, 2014), significant learning-related changes in GC neurons recorded from control animals were largely restricted to the late epoch of the response (>750ms; Figure 4a, left). This pattern is consistent with the generally agreed-upon suggestion that CTA changes the palatability of a taste, leaving taste identity intact (Bures et al, 1998;Fonseca et al, 2020), and with the fact that it is the transition into this late state that is implicated in the driving of palatability-related behavior (Li et al, 2016;Sadacca et al, 2016;Mukherjee et al, 2019).…”
Section: The Dynamics Of Learning-related Response Plasticity Is Abnormal In the Bla-specific Stk11 Kosupporting
confidence: 88%
“…Given the relatively small change in perceived salty and sweet taste intensities, these changes may not be biologically or clinically meaningful. However, previous studies have found that decreasing salt and sugar consumption reduced their respective perceived intensities [6,23], and perceived sucrose taste intensity (as well as palatability) may be a factor in overconsumption of sweet foods and beverages [24].…”
Section: Discussionmentioning
confidence: 90%
“…To investigate whether tesofensine impairs sucrose detection or palatability responses, we modified a psychophysical task using a new equipment called the homegustometer [ 32 , 46 ]. Rats performed the task day and night over multiple consecutive days, which allowed us to characterize the temporal pharmacological effects of tesofensine across days ( Fig 11A ) and within a day ( S3 Fig ).…”
Section: Resultsmentioning
confidence: 99%
“…To investigate whether tesofensine impairs sucrose detection or palatability responses, we modified a psychophysical task using a new equipment called the homegustometer [32,46]. Rats performed the task day and night over multiple consecutive days, which allowed us to characterize the temporal pharmacological effects of tesofensine across days (Fig 11A) and within a day (S3 Fig) . The rats (n = 4) were trained to discriminate between different concentrations of sugar and water using a homegustometer, and their performance was recorded continuously for up to 23 hours daily.…”
Section: Tesofensine Does Not Affect Sucrose Detection or Oromotor Pa...mentioning
confidence: 99%